Cationic electrodeposition coating composition, electrodeposition coating method, and cationic electrodeposition coating film
Patent Information
- Application Number
- JP2020200783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-03
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-12-03
AI Technical Summary
【0013】 本発明によれば、貯蔵安定性に優れるとともに低温硬化可能であり、かつ耐食性に優れた塗膜を形成できる、カチオン電着塗料組成物を提供できる。
Smart Images

Figure 0007634360000001 
Figure 0007634360000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a cationic electrodeposition coating composition, an electrodeposition coating method, and a cationic electrodeposition coating film. [Background technology]
[0002] Conventionally, cationic electrocoating paints are known that are used as undercoats for imparting corrosion resistance to industrial products such as automobiles. Cationic electrocoating paints contain, for example, an amino group-containing epoxy resin and a blocked polyisocyanate curing agent. Cationic electrocoating paints are required to have high corrosion resistance and rust resistance, as well as low VOC (volatile organic compounds) content, high adhesion, high hydrophobicity (blocking properties), and other properties.
[0003] In recent years, in order to reduce energy costs, techniques have been proposed for low-temperature curing electrodeposition paints that can reduce the baking temperature of electrodeposition coating films formed by electrodeposition paints. For example, a technique has been proposed for cationic electrodeposition paints in which a low-temperature curing blocked polyisocyanate compound, an amino group-containing epoxy resin, and a pigment dispersion paste are separately dispersed in water and mixed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 138445 Summary of the Invention [Problem to be solved by the invention]
[0005] The technology disclosed in Patent Document 1 cannot be said to have sufficiently improved the storage stability and corrosion resistance of the formed electrodeposition coating film, which are problems associated with low-temperature curing electrodeposition paints, and there is still room for improvement.
[0006] The present invention has been made in view of the above, and an object of the present invention is to provide a cationic electrodeposition coating composition which has excellent storage stability, can be cured at low temperatures, and can form a coating film having excellent corrosion resistance. [Means for solving the problem]
[0007] (1) The present invention relates to a cationic electrodeposition coating composition comprising an amino group-containing epoxy resin (A), a blocked polyisocyanate compound (B), and a pigment (C), wherein the blocked polyisocyanate compound (B) comprises a blocked polyisocyanate compound (B-1) obtained by blocking hexamethylene diisocyanate with 3,5-dimethylpyrazole, and at least a part of the blocked polyisocyanate compound (B) is a half-blocked half-blocked polyisocyanate curing agent, or the amino group-containing epoxy resin (A) is substantially free of primary amino groups.
[0008] (2) The cationic electrodeposition coating composition according to (1), wherein the content of the blocked polyisocyanate compound (B-1) is from 15% by mass to 45% by mass based on the total resin solid content.
[0009] (3) The cationic electrodeposition coating composition according to (1) or (2), wherein the content of the half-blocked polyisocyanate curing agent in the amino group-containing epoxy resin (A) having a primary amino group is 1% by mass or more and 10% by mass or less based on the total resin solid content other than the half-blocked polyisocyanate curing agent.
[0010] (4) A cationic electrodeposition coating composition according to any one of (1) to (3), wherein the content of the amino group-containing epoxy resin (A) substantially free of primary amino groups is 90 mass % or more based on the total mass of the amino group-containing epoxy resin (A).
[0011] (5) An electrodeposition coating method comprising: an electrodeposition step of immersing an object to be coated in the electrodeposition coating composition according to any one of (1) to (4) and applying a voltage to form a coating film; and a curing step of curing the coating film at a temperature of 140°C or less to obtain an electrodeposition coating film.
[0012] (6) The present invention also provides a cationic electrodeposition coating film formed from a cationic electrodeposition coating composition containing an amino group-containing epoxy resin (A), a blocked polyisocyanate compound (B), and a pigment (C), the cationic electrodeposition coating film having a wet coating film resistance of 1.0×10 8 (Ω cm 2 ) or more. Effect of the Invention
[0013] According to the present invention, there can be provided a cationic electrodeposition coating composition which has excellent storage stability, can be cured at low temperatures, and can form a coating film having excellent corrosion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the description of the following embodiments.
[0015] <Cationic electrodeposition coating composition> The cationic electrodeposition coating composition according to this embodiment can form an electrodeposition coating film having preferable corrosion resistance on the surface of the substrate by electrodeposition coating on the substrate, depositing a coating film, and then curing the coating film by low-temperature baking at, for example, 140°C or less. It also has preferable storage stability. The cationic electrodeposition coating composition according to this embodiment contains an amino group-containing epoxy resin (A), a blocked polyisocyanate compound (B), and a pigment (C).
[0016] (Amino group-containing epoxy resin (A)) The amino group-containing epoxy resin (A) is a coating film-forming resin in an electrodeposition coating. The amino group-containing epoxy resin (A) is obtained by modifying the oxirane ring (hereinafter sometimes referred to as "epoxy group") of an epoxy resin with an amine compound.
[0017] The epoxy resin, which is the starting material of the amino group-containing epoxy resin (A), is, for example, a polyphenol polyglycidyl ether type epoxy resin, which is a reaction product of a polycyclic phenol compound and epichlorohydrin. Examples of the polycyclic phenol compound include bisphenol A, bisphenol F, bisphenol S, phenol novolac, cresol novolac, etc. In this specification, the "polyphenol polyglycidyl ether type epoxy resin" includes polyphenol polyglycidyl ether type epoxy resin and a state in which a polycyclic phenol compound is subjected to a chain extension reaction.
[0018] In the modification of an epoxy resin with an amine compound, it is preferable to use an epoxy resin obtained by a chain extension reaction of a polyphenol polyglycidyl ether type epoxy resin and a polycyclic phenol compound. The conditions of the chain extension reaction are not particularly limited and can be appropriately selected depending on the stirring device used, the reaction scale, etc. The reaction conditions can be, for example, 85 to 180°C and 0.1 to 8 hours. More preferably, the reaction conditions can be 100 to 150°C and 2 to 8 hours. The stirring device used is not particularly limited and can be a stirring device commonly used in the paint field.
[0019] In addition to the above, the epoxy resin may be an oxazolidone ring-containing epoxy resin described in JP-A-5-306327. These epoxy resins can be prepared by reacting a diisocyanate compound or a bis-urethane compound obtained by blocking the isocyanate group of a diisocyanate compound with a lower alcohol such as methanol or ethanol with epichlorohydrin.
[0020] The epoxy resin may be a resin obtained by subjecting a part of the epoxy resin to a chain extension reaction before modification with an amine compound. For example, bifunctional polyester polyol, polyether polyol, dibasic carboxylic acid, etc. may be used for the chain extension reaction. Examples of the polyether polyol include polyols having a polyethylene oxide group and polyols having a polypropylene oxide group. Thus, for example, when a chain extension reaction is performed using a polyol having a polypropylene oxide group, a polypropylene oxide group-containing epoxy resin is obtained. The content of the polypropylene oxide group-containing epoxy resin is preferably 1 to 40 parts by mass, more preferably 15 to 25 parts by mass, relative to 100 parts by mass of the epoxy resin. Examples of epoxy resins having the same aspect as the polypropylene oxide group-containing epoxy resin include epoxy resins obtained by a chain extension reaction of a polyphenol polyglycidyl ether type epoxy resin, a polycyclic phenol compound, and a polypropylene oxide group-containing epoxy resin.
[0021] The amino group-containing epoxy resin (A) is obtained by reacting the epoxy group of the above-mentioned epoxy resin with an amine compound. When the blocked polyisocyanate compound (B) described later does not contain a half-blocked polyisocyanate curing agent, the amino group-containing epoxy resin (A) does not substantially have a primary amino group.
[0022] When at least a portion of the blocked polyisocyanate compound (B) is a half-blocked polyisocyanate compound, or when the amino group-containing epoxy resin (A) is an amino group-containing epoxy resin that has substantially no primary amino groups, the wet coating film resistance value (described later) of the formed electrodeposition coating film can be improved, and preferable corrosion resistance can be obtained.
[0023] (Amino group-containing epoxy resin (A) substantially not having primary amino groups) The amino group-containing epoxy resin (A) is obtained by reacting an epoxy resin with an amino compound, opening the oxirane ring of the epoxy resin, and introducing an amino group. The amino group-containing epoxy resin (A) according to the present embodiment preferably does not substantially have a primary amino group. This allows the wet coating film resistance value of the formed electrodeposition coating film to be improved, as described below, even when cured at a low temperature, and provides favorable corrosion resistance.
[0024] The amino group-containing epoxy resin (A) substantially free of primary amino groups can be obtained by using a diamine having a primary amino group not blocked with a ketone compound and a secondary or tertiary amino group as an amine compound. The primary amino group is not blocked with a ketone compound, but is consumed in the amine reaction of the epoxy resin and is used to form the branched chain of the amino group-containing epoxy resin (A). This allows the amino group-containing epoxy resin (A) substantially free of primary amino groups to be obtained.
[0025] The diamine having a primary amino group not blocked with the ketone compound and a secondary or tertiary amino group is not particularly limited, and for example, a diamine having a primary amino group and a tertiary amino group such as N,N-dimethyl-1,3-propanediamine, dimethylaminoethylamine, or a diamine having a hydroxyl group in addition to a primary amino group and a tertiary amino group such as N-(3-aminopropyl)diethanolamine is preferably used. By using the diamine having a hydroxyl group, a preferable coating film adhesion and curability can be obtained. In the above example, the number of primary amino groups not blocked with the ketone compound is one, and is not particularly limited and may be multiple, but is preferably one from the viewpoint of reaction control. The number of hydroxyl groups is also not particularly limited, and may be one or more.
[0026] In the amino group-containing epoxy resin (A) according to this embodiment, the content of the amino group-containing epoxy resin (A) that does not substantially have a primary amino group is preferably 90 mass% or more based on the total mass of the amino group-containing epoxy resin (A) in terms of storage stability.
[0027] The amine compound may be used in combination with other amine compounds than those mentioned above. For example, primary amines such as butylamine, octylamine, and monoethanolamine, secondary amines such as diethylamine, dibutylamine, methylbutylamine, diethanolamine, and N-methylethanolamine, complex amines such as diethylenetriamine, and tertiary amines such as triethylamine, N,N-dimethylbenzylamine, and N,N-dimethylethanolamine. The above amine compounds may be used alone or in combination with two or more.
[0028] As the amine compound, it is preferable to avoid using ketimine compounds as much as possible. This is because the formation of ketimine groups requires blocking with ketone compounds such as methyl isobutyl ketone, but the ketone compounds, which are VOCs, are generated during deblocking. It is not impossible to use ketimine compounds, and ketimine of aminoethylethanolamine, diketimine of diethylenetriamine, etc. can be used as necessary.
[0029] The amount of the amine compound is preferably 0.9 to 1.2 equivalents per equivalent of the epoxy group of the epoxy resin. In addition, the amino group-containing epoxy resin (A) obtained by reacting the epoxy resin with the amine compound preferably does not substantially have a primary amino group. In this specification, "substantially does not have a primary amino group" means that the ratio of primary amino groups to the amino groups in the amino group-containing epoxy resin (A) is 2% or less. The ratio of primary amino groups in the amino group-containing epoxy resin (A) can be confirmed by measuring the tertiary amine ratio, which is the ratio of tertiary amino groups to the amino groups in the amino group-containing epoxy resin (A). The ratio of the amino group-containing epoxy resin (A) that does not substantially have a primary amino group is 98% or more, preferably 99% or more, and more preferably 100%. Here, the tertiary amine ratio is the percentage obtained by dividing the tertiary amine value by the total amine value ((tertiary amine value) / (total amine value))×100, and can be determined by the following method.
[0030] (Tertiary amine value test method) (1) Weigh the sample into a 100 ml beaker. (2) Add 0.5g of pure water. (3) Dissolve the above sample in 50 g of THF (tetrahydrofuran). (4) Stir for 5 minutes. (5) Next, add 7.5 ml of acetic anhydride and 2.5 ml of acetic acid and stir at about 40°C for 5 minutes. (6) Using an automatic potentiometric titrator, titrate with 0.1N perchloric acid acetic acid solution. (7) Measure the tertiary amine value using the following formula. Tertiary amine value = (titer amount mL × factor × 10) / (sample amount g × solids amount)
[0031] (Total Amine Value Test Method) (1) Accurately weigh out 500 mg of sample into a 200 ml Erlenmeyer flask. (2) Add approximately 50 ml of glacial acetic acid and dissolve uniformly. (3) Add 5 to 6 drops of indicator methyl violet solution and mix uniformly. (4) Titrate with 0.1N perchloric acid and acetic acid solution, and the endpoint is when the solution turns bright green.
[0032] The reaction conditions for reacting the epoxy resin with the amine compound can be appropriately selected depending on the reaction scale, etc. Examples of the reaction conditions include reaction at 80 to 150° C. for 0.1 to 5 hours, preferably at 120 to 150° C. for 0.5 to 3 hours.
[0033] The number average molecular weight of the amino group-containing epoxy resin (A) is preferably in the range of 1,000 to 7,000. By having a number average molecular weight of 1,000 or more, the physical properties such as solvent resistance and corrosion resistance of the obtained cured electrodeposition coating film become good. On the other hand, by having a number average molecular weight of 7,000 or less, the viscosity of the amino group-containing epoxy resin (A) can be easily adjusted, enabling smooth synthesis. In addition, the obtained amino group-containing epoxy resin (A) can have a preferable dispersibility, making it easy to handle. The number average molecular weight of the amino group-containing epoxy resin (A) is more preferably in the range of 1,500 to 4,000.
[0034] The number average molecular weight can be measured under the following GPC system measurement conditions. Device name: alliance 2695 Separations Module Column: TSK gel ALPHA-M (Tosoh Corporation) Flow rate: 1.00ml / min Detector: alliance 2414 Refractive Index Detector Mobile phase: N,N'-dimethylformamide Standard samples: TSK STANDARD POLYSTYRENE (manufactured by Tosoh Corporation), A-500, A-2500, F-1, F-4, F-20, F-80, F-700, 1-phenylhexane (manufactured by Aldrich)
[0035] The amino group-containing epoxy resin (A) preferably has a milligram equivalent of base (MEQ(B)) per 100 g of resin solid content of 50 to 350. In particular, when the MEQ(B) is less than 50, the storage stability of the pigment dispersion paste may be poor. The milligram equivalent of base (MEQ(B)) per 100 g of solid content of the amino group-containing epoxy resin (A) can be adjusted by the type and amount of the amine compound reacted in the preparation of the amino group-containing epoxy resin (A).
[0036] MEQ(B) is an abbreviation for mg equivalent (base), which is the mg equivalent of base per 100 g of solid content of resin. This MEQ(B) can be measured by precisely weighing out about 5 g of the solid content of the electrodeposition coating composition, dissolving it in about 50 ml of a solvent (THF: tetrahydrofuran), and then performing potentiometric titration with a 0.1 N hydrochloric acid solution using an automatic potentiometric titrator (e.g., APB-710, manufactured by Kyoto Electronics Manufacturing Co., Ltd.) to quantitatively determine the amount of base contained in the amino group-containing epoxy resin (A).
[0037] The hydroxyl value of the amino group-containing epoxy resin (A) is preferably within the range of 150 to 650 mgKOH / g. When the hydroxyl value is 150 mgKOH / g or more, the curing property of the electrodeposition coating film is good, and the appearance of the coating film is also improved. On the other hand, when the hydroxyl value is 650 mgKOH / g or less, the amount of hydroxyl groups remaining in the electrodeposition coating film becomes appropriate, and there is no risk of reducing the water resistance of the coating film. The hydroxyl value of the amino group-containing epoxy resin (A) is more preferably within the range of 150 to 400 mgKOH / g. The hydroxyl value can be determined by a method according to JIS K 1557-1.
[0038] As the amino group-containing epoxy resin (A), multiple kinds of amino group-containing epoxy resins (A) having different number average molecular weight, MEQ (B) and hydroxyl value may be used in combination. In this case, the average MEQ (B) and average hydroxyl value calculated based on the mass ratio of each amino group-containing epoxy resin (A) are preferably within the above range. An example of using multiple kinds of amino group-containing epoxy resins (A) in combination is, for example, an amino group-containing epoxy resin (A) having MEQ (B) of 50-200 and hydroxyl value of 50-300 mgKOH / g and an amino group-containing epoxy resin (A) having MEQ (B) of 200-350 and hydroxyl value of 200-500 mgKOH / g in combination. The above combination increases the hydrophobicity of the core part and the hydrophilicity of the shell part of the emulsion, and thus can impart better corrosion resistance to the formed electrodeposition coating film.
[0039] The resin component may contain a resin other than the amino group-containing epoxy resin (A). For example, an amino group-containing acrylic resin, an amino group-containing polyester resin, etc. may be contained as necessary. In addition to the amino group-containing resin, for example, an acrylic resin, a polyester resin, a urethane resin, a butadiene resin, a phenol resin, a xylene resin, etc. may be contained. Examples of the phenol resin and the xylene resin include resins having 2 to 10 aromatic rings.
[0040] (Blocked polyisocyanate compound (B)) The blocked polyisocyanate compound (B) is prepared by blocking a polyisocyanate with a blocking agent. The blocked polyisocyanate compound (B) reacts preferentially with the amino group of the amino group-containing epoxy resin (A), and if the amino group-containing epoxy resin (A) has a hydroxyl group, it further reacts with the hydroxyl group to harden and form an electrodeposition coating film.
[0041] The polyisocyanate may be hexamethylene diisocyanate (hereinafter, sometimes referred to as "HDI"). The blocking agent may be 3,5-dimethylpyrazole (hereinafter, sometimes referred to as "DMP"). The blocked polyisocyanate compound (B-1) obtained by blocking the HDI with DMP improves the reactivity of the cationic electrodeposition coating composition, and favorable low-temperature curing properties are obtained. The blocked polyisocyanate compound (B-1) obtained by blocking the HDI with DMP is preferably contained in an amount of 15% by mass or more and 45% by mass or less in terms of mass ratio to the total resin solid content. If the mass ratio to the total resin solid content is 15% by mass or less, the wet coating film resistance is reduced and the corrosion resistance is reduced, and if it is 45% by mass or more, the corrosion resistance is reduced due to a reduction in adhesion functional groups.
[0042] The blocked polyisocyanate compound (B) may contain a blocked polyisocyanate compound (B) other than the blocked polyisocyanate compound (B-1) in which the above HDI is blocked with DMP. In the above case, examples of the polyisocyanate include aliphatic diisocyanates such as tetramethylene diisocyanate and trimethylhexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and 4,4'-methylenebis(cyclohexyl isocyanate), and aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, and xylylene diisocyanate.
[0043] Similarly, examples of blocking agents other than DMP include monovalent alkyl or aromatic alcohols such as n-butanol, n-hexyl alcohol, 2-ethylhexanol, lauryl alcohol, phenol carbinol, and methylphenyl carbinol; cellosolves such as ethylene glycol monohexyl ether and ethylene glycol mono 2-ethylhexyl ether; polyether-type diols terminated at both ends such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol phenol; polyester-type polyols terminated at both ends obtained from diols such as ethylene glycol, propylene glycol, and 1,4-butanediol and dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, suberic acid, and sebacic acid; phenols such as para-t-butylphenol and cresol; oximes such as dimethyl ketoxime, methyl ethyl ketoxime, methyl isobutyl ketoxime, methyl amyl ketoxime, and cyclohexanone oxime; and lactams represented by ε-caprolactam and γ-butyrolactam.
[0044] (Half-blocked polyisocyanate curing agent) The half-blocked polyisocyanate curing agent is a polyisocyanate compound in which a part of the isocyanate groups is blocked with a known blocking agent. The reaction between the polyisocyanate compound and the blocking agent is preferably carried out by cooling to 40 to 50°C while dropping the blocking agent under stirring, if necessary, in the presence of a catalyst.
[0045] The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups on average in one molecule, and for example, the diisocyanate compound used in the preparation of the blocked polyisocyanate compound (B) described above can be used. Examples of blocking agents used to prepare the half-blocked polyisocyanate include lower aliphatic alkyl monoalcohols having 4 to 20 carbon atoms. Specific examples include butyl alcohol, amyl alcohol, hexyl alcohol, 2-ethylhexyl alcohol, and heptyl alcohol.
[0046] The content of the half-blocked polyisocyanate curing agent is preferably 1% by mass or more and 10% by mass or less based on the total resin solid content other than the half-blocked polyisocyanate compound. If the content is less than 1% by mass, the effect of improving the wet coating film resistance value is not sufficiently obtained. If the content is more than 10% by mass, the adhesion of the coating film decreases due to the decrease in the adhesion functional group.
[0047] As the curing agent, a curing agent other than the blocked polyisocyanate compound (B) and the half-blocked polyisocyanate compound may be used in combination. For example, at least one curing agent selected from the group consisting of organic curing agents such as melamine resins and phenolic resins, silane coupling agents, and metal curing agents may be used.
[0048] (Pigment (C)) As the pigment (C), inorganic or organic pigments that are usually used in electrodeposition coating compositions can be used. For example, color pigments such as titanium white (titanium dioxide), carbon black, and red iron oxide; extender pigments such as kaolin, talc, aluminum silicate, calcium carbonate, mica, and clay; and rust-preventive pigments such as iron phosphate, aluminum phosphate, calcium phosphate, aluminum tripolyphosphate, aluminum phosphomolybdate, and aluminum zinc phosphomolybdate can be mentioned.
[0049] The pigment (C) is prepared in advance as a pigment dispersion paste by mixing the pigment and the pigment dispersion resin and dispersing them in an aqueous medium. This allows the powdery pigment to be uniformly dispersed in the electrodeposition coating composition. The pigment dispersion resin is not particularly limited, and examples of the pigment dispersion resin include cationic or nonionic low molecular weight surfactants and cationic polymers such as modified epoxy resins having quaternary ammonium groups and / or tertiary sulfonium groups. The aqueous medium includes ion-exchanged water and water containing a small amount of alcohol.
[0050] The content of the pigment dispersion resin in the pigment dispersion paste is not particularly limited, and can be, for example, 20 to 100 parts by mass in terms of the resin solid content ratio per 100 parts by mass of the pigment.
[0051] The solid content of the pigment dispersion paste is not particularly limited, and can be, for example, 40 to 70% by mass with respect to the total amount of the pigment dispersion paste.
[0052] The pigment dispersion paste can be obtained, for example, by mixing a pigment and a pigment dispersion resin, and then dispersing the mixture using a known dispersing device such as a ball mill or a sand grinding mill until the pigment particles in the mixture have a predetermined uniform particle size.
[0053] (Other Ingredients) The cationic electrodeposition paint according to the present embodiment may contain components other than those mentioned above. For example, it may contain a zinc compound, a Group 3 element compound, a bismuth compound, etc. This can improve the rust prevention of the electrodeposition coating film formed. Examples of zinc compounds include metal nitrites such as calcium nitrite, sodium nitrite, potassium nitrite, magnesium nitrite, strontium nitrite, barium nitrite, and zinc nitrite. Examples of the Group 3 element compounds include lanthanum oxide, lanthanum hydroxide, neodymium oxide, neodymium hydroxide, a mixture of lanthanum oxide and an organic acid, a mixture of lanthanum hydroxide and an organic acid, a mixture of neodymium oxide and an organic acid, a mixture of neodymium hydroxide and an organic acid, and the like. Examples of the bismuth compounds include bismuth oxide, bismuth hydroxide, a mixture of bismuth oxide and an organic acid, a mixture of bismuth hydroxide and an organic acid, and the like.
[0054] The cationic electrodeposition coating composition according to the present embodiment may contain additives generally used in the coating field. For example, organic solvents such as ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, ethylene glycol monoethylhexyl ether, propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, and propylene glycol monophenyl ether, surfactants such as drying inhibitors and defoamers, viscosity modifiers such as acrylic resin fine particles, anti-repellent agents, and inorganic rust inhibitors such as vanadium salts, copper, iron, manganese, magnesium, and calcium salts may be included as necessary. In addition to the above, known auxiliary complexing agents, buffers, smoothing agents, stress relaxation agents, gloss agents, semi-gloss agents, antioxidants, and ultraviolet absorbers may be blended according to the purpose. These additives may be added during the production of the resin emulsion described below, may be added during the production of the pigment dispersion paste, or may be added during or after the mixing of the resin emulsion and the pigment dispersion paste.
[0055] The cationic electrodeposition coating composition according to the present embodiment preferably has a pH of 4.5 to 7.0. If the pH of the cationic electrodeposition coating composition is less than 4.5, the amount of acid present in the cationic electrodeposition coating composition may be excessive, which may result in poor coating film appearance or coating workability. On the other hand, if the pH exceeds 7.0, the filterability of the cationic electrodeposition coating composition may decrease, and the horizontal appearance of the cured electrodeposition coating film may decrease. The pH of the cationic electrodeposition coating composition can be set within the above range by adjusting the amount of neutralizing acid used, the amount of free acid added, etc. The pH is more preferably 5.0 to 7.0. The pH can be measured using a commercially available pH meter with a temperature compensation function.
[0056] <Method of producing cationic electrodeposition coating composition> The cationic electrodeposition coating composition according to this embodiment can be prepared and manufactured by mixing a resin emulsion containing an amino group-containing epoxy resin (A) and a blocked polyisocyanate compound (B), a pigment paste containing a pigment (C), and other components by a conventionally known method.
[0057] In the cationic electrodeposition coating composition according to the present embodiment, the solid content is preferably adjusted to be in the range of 15 to 25% by mass. The solid content can be adjusted by using an aqueous solvent. Examples of the aqueous solvent include ion-exchanged water and pure water.
[0058] <Cation electrodeposition coating method> An electrodeposition coating film can be formed on the surface of a substrate by electrodeposition coating the substrate using the cationic electrodeposition coating composition according to this embodiment. The cationic electrodeposition coating method according to this embodiment includes an electrodeposition step of forming a coating film by immersing the substrate in the electrodeposition coating composition and applying a voltage thereto, and a curing step of curing the coating film at a temperature of 140°C or less to obtain an electrodeposition coating film.
[0059] (electrodeposition process) In the electrodeposition process, the substrate is used as a cathode and a voltage is applied between the cathode and the anode, whereby an electrodeposition coating is deposited on the substrate. The substrate is not particularly limited as long as it is made of a material capable of passing electricity, and examples thereof include cold-rolled steel sheets, hot-rolled steel sheets, stainless steel, electrogalvanized steel sheets, hot-dip galvanized steel sheets, zinc-aluminum alloy-based plated steel sheets, zinc-iron alloy-based plated steel sheets, zinc-magnesium alloy-based plated steel sheets, zinc-aluminum-magnesium alloy-based plated steel sheets, aluminum-based plated steel sheets, aluminum-silicon alloy-based plated steel sheets, and tin-based plated steel sheets.
[0060] In the electrodeposition step, the substrate is immersed in the electrodeposition coating composition, and then a voltage of 50 to 450 V is applied to perform electrodeposition coating. If the applied voltage is less than 50 V, the electrodeposition may be insufficient, and if it exceeds 450 V, the coating film appearance may be poor. During electrodeposition coating, the bath temperature of the coating composition is adjusted to, for example, 10 to 45°C. The time for applying the voltage varies depending on the electrodeposition conditions, but can be, for example, 2 to 5 minutes. After the above electrodeposition step, a step of washing the electrodeposition coating film with water may be provided as necessary.
[0061] (hardening process) In the curing step, the coating film deposited in the electrodeposition step is heated at a temperature of 140° C. or less for, for example, 10 to 30 minutes. The electrodeposition coating film is cured by the above curing step. In the curing step according to the present embodiment, curing at a lower temperature than the curing temperature of a normal electrodeposition coating film is possible.
[0062] <Cationic electrodeposition coating> The cationic electrodeposition coating film formed on the above-mentioned substrate has a wet coating resistance of 1.0×10 8 (Ω cm 2) or more. The higher the wet coating resistance value, the better the cationic electrocoating film is at blocking polar molecules such as water, and the better the blocking properties of the cationic electrocoating film. The wet coating resistance value can be measured, for example, by the following method. A cationic electrocoating film is deposited on a substrate, and a hardened test piece is placed in a measurement cell. Ion-exchanged water is then poured into the measurement cell, and the measurement cell is maintained in a thermostatic chamber (55°C). An AC voltage of 0.5V (wave height: ±0.5V, wavelength: 1 minute square wave pulse) is then applied between the test piece and the electrode for 1 minute, and the resistance value of the coating film is measured. For example, the average value of five measurements made using the above method can be used as the wet coating resistance value.
[0063] When a cationic electrodeposition coating film is formed using the electrodeposition coating composition according to this embodiment, even when the coating film is cured at a low temperature of 140° C. or less, the wet coating film resistance is 1.0×10 8 (Ω cm 2 ) or more.
[0064] The cationic electrocoating film preferably has a thickness of 5 to 60 μm, more preferably 20 to 45 μm, after curing. If the thickness of the electrocoating film is less than 5 μm, the rust prevention properties may be insufficient. EXAMPLES
[0065] The present invention will be described in more detail below based on examples. The present invention is not limited to the following examples. In the examples, "parts" and "%" are based on mass unless otherwise specified. In addition, the units of numerical values in Tables 1 and 2 are parts by mass unless otherwise specified. However, Examples 6 and 7 are reference examples.
[0066] (Production Example 1-A: Production of aminated epoxy resin (resin A)) 44 parts of butyl cellosolve, 940 parts of bisphenol A type epoxy resin (trade name DER-331J, manufactured by Dow Chemical Co.), 236 parts of bisphenol A, and 216 parts of octylic acid were mixed and heated to 120°C. Then, 1 part of dimethylbenzylamine was added, and the temperature in the reaction vessel was kept at 140°C. The reaction was continued until the epoxy equivalent reached 1043g / eq, and then the reaction vessel was cooled to 120°C. Next, a mixture of 54 parts of diethanolamine, 161 parts of diethylenetriamine diketimine (a methyl isobutyl ketone solution with a solid content concentration of 73%), and 24 parts of N-methylethanolamine was added, and the reaction was continued for 1 hour at 120°C to obtain an aminated epoxy resin (cation-modified epoxy resin: resin A).
[0067] (Production Example 1-B Production of aminated epoxy resin (resin B)) 10 parts of butyl cellosolve, 940 parts of bisphenol A type epoxy resin (trade name DER-331J, manufactured by Dow Chemical Company), 254 parts of bisphenol A, and 80 parts of phenol were mixed and heated to 120°C. Then, 2 parts of dimethylbenzylamine were added, and the temperature in the reaction vessel was kept at 120°C. The reaction was allowed to proceed until the epoxy equivalent reached 700 g / eq, and then the reaction vessel was cooled to a temperature of 110°C. Next, a mixture of 90 parts of diethanolamine and 44 parts of N,N-dimethyl-1,3-propanediamine was added, and the reaction was allowed to proceed for 1 hour at 110°C, to obtain an aminated epoxy resin (cation-modified epoxy resin: resin B).
[0068] (Production Example 2-A: Production of Half-Blocked Polyisocyanate Curing Agent (Curing Agent A)) 87 parts of 2,4 / 2,6-tolylene diisocyanate (trade name TDI-80, manufactured by Mitsubishi Chemical Dow Corporation) and 10 parts of methyl isobutyl ketone were mixed, and 73 parts of 2-ethylhexanol was added dropwise over 2.5 hours so that the temperature did not exceed 50° C. After that, it was confirmed that the NCO equivalent was 330 to 370, and a half-blocked polyisocyanate curing agent (curing agent A) was obtained (solid concentration 94%).
[0069] (Production Example 2-B: Production of blocked polyisocyanate curing agent (curing agent B)) 160 parts of an isocyanurate of hexamethylene diisocyanate (trade name Sumidur N3300, manufactured by Sumika Bayer Urethane Co., Ltd.) and 24 parts of MIBK were charged into a reaction vessel and heated to 60°C. 80 parts of 3,5-dimethylpyrazole were added thereto over 2 hours. After further heating at 70°C for 2 hours, it was confirmed that the absorption due to the isocyanate group had disappeared in the measurement of the IR spectrum. Then, 36 parts of butyl cellosolve were added to obtain a blocked polyisocyanate curing agent (curing agent B) (solid concentration 82%).
[0070] (Production Example 2-C: Production of blocked polyisocyanate curing agent (curing agent C)) 165 parts of an isocyanurate of hexamethylene diisocyanate (trade name Sumidur N3300, manufactured by Sumika Bayer Urethane Co., Ltd.) and 24 parts of MIBK were charged into a reaction vessel and heated to 60°C. 75 parts of methyl ethyl ketoxime (MEK oxime) were added dropwise over 2 hours. After further heating at 70°C for 2 hours, it was confirmed that the absorption due to the isocyanate group had disappeared in the measurement of the IR spectrum. Then, 36 parts of butyl cellosolve were added to obtain a blocked polyisocyanate curing agent (curing agent B) (solid concentration 82%).
[0071] (Production Example 3: Preparation of pigment dispersing resin) In a reaction vessel equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 2220 parts of isophorone diisocyanate, 342.1 parts of methyl isobutyl ketone, 2.2 parts of dibutyltin laurate and 878.7 parts of methyl ethyl ketone oxime were charged. After that, the mixture was kept at 60°C for 1 hour, and it was confirmed that the NCO equivalent was 348, and 890 parts of dimethylethanolamine were charged. After keeping the mixture at 60°C for 1 hour and confirming that the NCO peak had disappeared by IR, 1872.6 parts of 50% lactic acid and 495 parts of deionized water were charged to obtain a quaternizing agent. Next, 870 parts of tolylene diisocyanate and 49.5 parts of methyl isobutyl ketone were charged in a different reaction vessel, and 667.2 parts of 2-ethylhexanol were dropped over 2.5 hours. After the dropwise addition, 35.5 parts of methyl isobutyl ketone were charged and the mixture was kept warm for 30 minutes. Thereafter, it was confirmed that the NCO equivalent was 330 to 370, and a half-blocked polyisocyanate was obtained.
[0072] In a reaction vessel equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 940.0 parts of bisphenol A type epoxy resin (trade name DER-331J, manufactured by Dow Chemical Co.) was diluted with 38.5 parts of methanol, and then 0.1 parts of dibutyltin dilaurate, 87.1 parts of tolylene diisocyanate and 1.4 parts of N,N-dimethylbenzylamine were added thereto and kept at 130°C for 2 hours. At this time, methanol was fractionated using a fractionating tube. This was cooled to 115°C, and methyl isobutyl ketone was added until the solid content concentration reached 90%, after which 270.3 parts of bisphenol A and 39.2 parts of 2-ethylhexanoic acid were added and heated and stirred at 125°C for 2 hours, after which 516.4 parts of the half-block polyisocyanate was dropped over 30 minutes, and then heated and stirred for 30 minutes. 1506 parts of polyoxyethylene bisphenol A ether was gradually added and dissolved. After cooling to 90°C, the above quaternizing agent was added, and the mixture was kept at 70 to 80°C and the acid value was confirmed to be 2 or less, to obtain a pigment dispersion resin (resin solids concentration 30%).
[0073] (Production Example 4: Preparation of pigment dispersion paste) A sand grinding mill was charged with 106.9 parts of the pigment dispersion resin obtained in Production Example 3, 1.6 parts of carbon black, 40 parts of kaolin, 55.4 parts of titanium dioxide, 3 parts of aluminum phosphomolybdate, and 13 parts of deionized water, and the mixture was dispersed until the particle size reached 10 μm or less, thereby obtaining a pigment dispersion paste (solids concentration 60%).
[0074] (Production Example 5-A: Production of electrocoating resin emulsion (EmA)) 300g (solid content) of the resin (Resin A) obtained in Production Example 1-A, 16g (solid content) of the half-blocked polyisocyanate curing agent obtained in Production Example 2-A, and 100g (solid content) of the blocked polyisocyanate curing agent obtained in Production Example 2-B were mixed, and ethylene glycol mono-2-ethylhexyl ether was added so that the solid content was 3% (12.5g). Next, formic acid was added to neutralize the mixture to a neutralization rate of 30%, and ion-exchanged water was added to slowly dilute the mixture, and an electrodeposition paint resin emulsion (EmA) with a solid content concentration of 41% was obtained.
[0075] (Production Examples 5-B to 5-L: Production of Electrodeposition Paint Resin Emulsions (EmB to L)) Except for preparing the compositions shown in Table 1, the same procedure as in Production Example 5-A was followed to obtain electrodeposition paint resin emulsions (EmB to EmH).
[0076] <Example 1> 1,394 g of ion-exchanged water, 560 g of resin emulsion (EmA) and 41 g of the pigment dispersion paste obtained in Production Example 4 were added to a stainless steel container, and the mixture was then aged at 40° C. for 16 hours to form an electrodeposition coating composition.
[0077] <Examples 2 to 8 and Comparative Examples 1 to 4> For Examples 2 to 8 (EmB to EmH) and Comparative Examples 1 to 4 (EmI to EmL), electrodeposition coating compositions were obtained in the same manner as in Example 1, except that the compositions were prepared according to the formulations shown in Tables 1 and 2.
[0078] [Table 1]
[0079] <Evaluation> The electrodeposition coating compositions according to the above Examples and Comparative Examples were used and evaluated under the following conditions.
[0080] [Gel fraction (curability) evaluation] The electrodeposition coating compositions according to the above examples and comparative examples were deposited on a tin plate whose weight had been measured in advance, so that the thickness of the dried coating film was 20 μm. The coating film was then cured by baking at 130° C. for 10 minutes, forming a cationic electrodeposition coating film on the tin plate. The weight of the obtained test plate was measured, and the plate was immersed in acetone and refluxed for 6 hours, and then dried at 105° C. for 20 minutes. The weight after drying was measured, and the gel fraction was calculated by the following formula (1). The curability was evaluated according to the gel fraction value according to the following criteria, with A and B being considered as acceptable. The results are shown in Table 2. Gel fraction (%) = (W2 - W0) / (W1 - W0) × 100 (1) In formula (1), W0 is the weight of the tinplate, W1 is the weight of the coated plate after baking, and W2 is the weight of the coated plate after immersion in acetone.
[0081] A: Gel fraction 95% or more B: Gel fraction 90% or more and less than 95% C: Gel fraction 85% or more and less than 90% D: Gel fraction less than 85%
[0082] [Storage stability (MEQ(B) evaluation)] The MEQ (B) of each of the above examples and comparative examples was measured by the following method. First, about 10 g of the solid content of the electrodeposition coating composition was precisely weighed and dissolved in about 50 ml of a solvent (THF: tetrahydrofuran), and then 7.5 ml of acetic anhydride and 2.5 ml of acetic acid were added, and potentiometric titration was performed with a 0.1N perchloric acid acetic acid solution using an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., APB-410) to measure the base content in the amino group-containing epoxy resin. Then, the electrodeposition coating composition of each of the examples and comparative examples was stored at 40°C for 14 days, and the MEQ (B) was measured in the same manner. The change (%) in MEQ (B) before and after the storage test was calculated and evaluated according to the following evaluation criteria, with A, B, and C being considered as passing. The results are shown in Table 2. A: Less than 5% B: 5% or more but less than 10% C: 10% or more but less than 20% D: 20% or more
[0083] (Manufacturing of painted boards) A cold-rolled steel sheet (JISG3141, SPCC-SD) was immersed in Surf Cleaner EC90 (manufactured by Nippon Paint Co., Ltd.) at 50°C for 2 minutes to perform degreasing. Next, the sheet was immersed in a zirconium conversion treatment solution containing 0.005% ZrF and adjusted to pH 4 using NaOH at 40°C for 90 seconds to perform zirconium conversion treatment. Next, the electrodeposition coating composition obtained in the examples and comparative examples was added with a required amount of 2-ethylhexyl glycol so that the film thickness of the electrodeposition coating film after curing was 20 μm, and then the steel sheet was immersed, and a voltage was applied under the conditions of a 30-second increase to 180 V and then maintained for 150 seconds to deposit an uncured electrodeposition coating film on the coated object. The obtained uncured electrodeposition coating film was baked and cured at 130°C for 15 minutes to obtain a coated sheet having a cationic electrodeposition coating film. The above-mentioned coated sheet was used to perform the following SDT test.
[0084] [Hot salt water immersion test (SDT test)] The coating film of each of the coated panels of the Examples and Comparative Examples obtained above was scratched with a knife so as to reach the substrate, and the coated panels were immersed in 5% saline at 55°C for 240 hours. The coating film was then visually inspected for rust or blisters from the linear scratch and evaluated according to the following criteria. A, B, and C were deemed acceptable. The results are shown in Table 2. A: Maximum peeling width 4mm or less B: Maximum peeling width more than 4mm to less than 8mm C: Maximum peel width: 8mm to 10mm D: Maximum peel width over 10mm
[0085] [Wet paint film resistance measurement] A cold-rolled steel sheet (JIS G3141 SPCC-SD) was degreased using Surf Cleaner 53 manufactured by Nippon Paint Co., Ltd. The obtained steel sheet was subjected to a chemical conversion treatment using a zinc phosphate treatment agent SD-6350 (manufactured by Nippon Paint Co., Ltd.). The steel sheet subjected to the chemical conversion treatment was electrocoated using the cationic electrodeposition coating composition of each of the Examples and Comparative Examples so that the film thickness of the dried coating film was 15 μm, and this was baked at 160° C. for 15 minutes to be cured, thereby obtaining a cured electrodeposition coating film (test piece).
[0086] The wet coating resistance of the cured electrodeposition coating (test piece) obtained above was measured using a wet coating resistance measuring device. The substrate having the cured electrodeposition coating corresponds to a cold-rolled steel sheet (JIS G3141 SPCC-SD) after the electrodeposition coating was formed, and the high resistance meter used was a KEITHLEY 6517A ELECTROMETER / HIGH RESISTANCE METER.
[0087] The measurement conditions were as follows: The test piece was placed in a measurement cell, and then 50 mL of ion-exchanged water was poured into the measurement cell. The measurement cell was placed in a thermostatic bath (55°C) and the liquid temperature in the cell was maintained at 55°C.
[0088] A 0.5V AC voltage (wave height: ±0.5V, wavelength: 1 minute square wave pulse) was applied between the test piece and the electrode for 1 minute, and the wet coating resistance was measured. The average value after 5 measurements was taken as the wet coating resistance.
[0089] The higher the wet coating resistance, the more polar molecules such as water can be blocked, and the better the blocking ability of the electrodeposition coating. The wet coating resistance was evaluated according to the following evaluation criteria. A, B, and C were considered to be acceptable. The results are shown in Table 2.
[0090] A: 1×10 10 Ω cm 2 End B: 1×10 9 Ω cm 2 Over 10 10 Ω cm 2 less than C:1×10 8 Ω cm 2 Over 10 9 Ω cm 2 less than D: 1×10 8 Ω cm 2 less than
[0091] [Table 2]
[0092] From the results in Table 2, it was confirmed that the electrodeposition coating compositions of each Example have superior storage stability, good low-temperature curing properties, and are capable of forming cationic electrodeposition coating films with excellent corrosion resistance, compared to the electrodeposition coating compositions of each Comparative Example.
Claims
1. A cationic electrodeposition coating composition comprising an amino group-containing epoxy resin (A), a blocked polyisocyanate compound (B), and a pigment (C), The blocked polyisocyanate compound (B) includes a blocked polyisocyanate compound (B-1) in which hexamethylene diisocyanate is blocked with 3,5-dimethylpyrazole, At least a part of the blocked polyisocyanate compound (B) is a half-blocked half-blocked polyisocyanate curing agent, A cationic electrodeposition coating composition, wherein the content of the half-blocked polyisocyanate curing agent in the amino group-containing epoxy resin (A) substantially has a primary amino group is 1 mass % or more and 10 mass % or less based on the total resin solid content other than the half-blocked polyisocyanate curing agent.
2. 2. The cationic electrodeposition coating composition according to claim 1, wherein the content of the blocked polyisocyanate compound (B-1) is 15% by mass or more and 45% by mass or less based on the total resin solid content.
3. an electrodeposition step of immersing a substrate in the electrodeposition coating composition according to claim 1 or 2 and applying a voltage to the substrate to form a coating film; and a curing step of curing the coating film at a temperature of 140°C or less to obtain an electrodeposition coating film.
Citation Information
Patent Citations
Cationic electrodeposition coating composition
JP2002060680A
Aqueous coating composition and coated metal plate using thereof
JP2004277664A
Cationic electrodeposition coating material composition
JP2010024288A
Thermosetting coating composition
JP2016138203A
Cationic electrodeposition coating composition
JP2020164626A